An open-label prospective clinical study to assess the efficacy of increasing levocetirizine dose up to four times in chronic spontaneous urticaria not controlled with standard dose. (18th August 2017) - Sharma, Vinod Kumar; Gupta, Vishal; Pathak, Mona; Ramam, M.
Abstract: Objective: The EAACI/GA 2 LEN/EDF/WAO recommendation of increasing antihistamines' dose up to four times in urticaria not adequately controlled with the standard dose is largely based on expert opinion. The objective of this study is to test the current urticaria guidelines of up-dosing antihistamines as second-line treatment. Methods: This was an open-label study conducted prospectively on 113 patients with chronic spontaneous urticaria. All patients were treated with sequentially increasing doses of levocetrizine (5 mg, 10 mg, 15 mg and 20 mg/day) every week till the patients became completely asymptomatic or dose of 20 mg/day reached. Urticaria Activity Score (UAS)-7, urticaria-related quality-of-life (CU-Q2oL) and patients' global assessment were used to assess treatment response. Results: Twenty-one (18.58%) patients became asymptomatic with levocetirizine 5 mg/day, while 50 required higher doses of levocetirizine for complete control: 29/92 (31.52%), 6/63 (9.52%) and 15/57 (26.31%) with 10 mg, 15 mg and 20 mg/day, respectively. The percentage of patients experiencing >75% improvement increased with increasing doses of levocetirizine: 26.54%, 53.98%, 60.17% and 69.91% with 5 mg, 10 mg, 15 mg and 20 mg/day, respectively. Sequential up-dosing of levocetirizine produced a progressive improvement in both urticaria control (UAS-7) and quality-of-life (CU-Q2oL) without significantly increasing somnolence. Conclusions: Our results support the current recommendations of increasing antihistamines up to four times the standard dose in patients who fail the first-line treatment.